(3GdQSGdI GdOGeZI ddaGSb GdQO Ydi GdfUjQi dYfg Gddgs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj,J (B433 (3g` s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdi SHMGfg CeG HYO CjOce Gdehdi HJCjjOg Gfg hQO Edi cJGH Cdag HYV GdfUjQjI GdcGaQjf HehdGfG Ld PcQg GdeTQcjf Hg acJHJ gPg GdQSGdI QOkG Ydi eG Cdag gPG GdaGSb s
(3BNQgG (B:s
(3abO GbJQHJ GdSGYI hGfTb GdbeQ fYe GdfUjQ GdeYjf JeJ GdQSGdI hGdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3QSGdI ef QSGFd GdOQhRs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3fSNI KGdKI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B79s
Keywords: (3GdJhMjO hGdedd hGdfMds